THE EFFECT OF INFLUENCERS IN DIGITAL MARKETING ON PURCHASE DECISIONS OF UNPRI STUDENTS USING SKINCARE PRODUCTS - Bella Tobing; Willy Mulia Panjaitan; Mohd. Nawi Purba (Jurnal Ipteks Terapan, 2023)
In today's era, there are more and more marketing technologies that make it easy to market the products you want to market. Influencers and digital marketing are currently popular and widely used. The context of this research is to find out how influencers in digital marketing influence purchasing decisions of UNPRI students who use skincare products using qualitative methods. Where to find , analyze , record and describe subject perspectives by observing and interviewing UNPRI students who use skincare. It can be concluded that influencers in digital marketing help UNPRI students to be able to find information, evaluate, choose and use the skincare products they want to use, but they must do research that is accurate about the skincare products used